Information Hospitality, Academic Libraries, and Open Access - Joshua M Avery (Theological Librarianship, 2023)
This essay argues that a new concept of information hospitality should serve as an ethical imperative for librarians, and libraries, to be involved in the production and dissemination of open resources. Defined as meeting the information needs of neighbors and strangers by granting them access into the scholarly conversation, information hospitality finds support and context in the ancient and scriptural virtue of hospitality. Both ancient and scriptural hospitality had four traits: it was welcoming of both stranger and neighbor, as much as possible needs are met, it was to be freely given, and it was expressed by both individuals and institutions. All four of these traits are present in meeting the information needs of neighbors and strangers through the open scholarship.